2013
DOI: 10.1097/qad.0000000000000039
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive discontinuation and switching among couples receiving integrated HIV and family planning services in Lusaka, Zambia

Abstract: Objective To describe predictors of contraceptive method discontinuation and switching behaviors among HIV positive couples receiving couples' voluntary HIV counseling and testing services in Lusaka, Zambia. Design Couples were randomized in a factorial design to two family planning educational intervention videos, received comprehensive family planning services, and were assessed every 3-months for contraceptive initiation, discontinuation and switching. Methods We modeled factors associated with contrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 35 publications
3
46
3
1
Order By: Relevance
“…This is contrary to the notion that couples counseling leads to high modern FP uptake as it leads to increased spousal communication, which could then lead to increased knowledge and comfort in communicating FP issues [20, 21]. Our results are, however, similar to results of studies done in Jordan and Zambia, which found that the effect of couples versus individual counseling was statistically not significant [6, 22]. The lack of difference in modern FP uptake in our study may be secondary to the fact that only those who agreed to FP counseling were included in our study, which may imply that they already had an interest in FP use, which then led to high FP uptake.…”
Section: Discussioncontrasting
confidence: 96%
“…This is contrary to the notion that couples counseling leads to high modern FP uptake as it leads to increased spousal communication, which could then lead to increased knowledge and comfort in communicating FP issues [20, 21]. Our results are, however, similar to results of studies done in Jordan and Zambia, which found that the effect of couples versus individual counseling was statistically not significant [6, 22]. The lack of difference in modern FP uptake in our study may be secondary to the fact that only those who agreed to FP counseling were included in our study, which may imply that they already had an interest in FP use, which then led to high FP uptake.…”
Section: Discussioncontrasting
confidence: 96%
“…98,99 All 12 intervention studies were conducted in sub-Saharan Africa. FP interventions included a facilitated referral model, 61 integration of FP services into HIV clinical care, 62,6468 an education video to promote long-acting methods of contraception, 63,70,71 and group education sessions. 69 …”
Section: Resultsmentioning
confidence: 99%
“…We estimated HIV acquisition risk related to contraceptive implants. Contraception was provided at the research site and was measured frequently to capture high rates of stopping and switching; in our cohorts, we have observed that about 25% of women switch methods during follow-up, with most discontinuation/switching observed among injectable (34%) and IUD (33%) users [13,22]. This is one of few studies to differentiate between genetically linked versus unlinked infections, important when modeling index partner covariates.…”
Section: Discussionmentioning
confidence: 98%